FORMATION OF STUDENTS’ INFORMATION COMPETENCE WHEN STUDYING PHYSICS BY COMPUTER SIMULATION - Silveistr, Anatolii; Mokliuk, Mykola; Kolomiiets, Taras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article describes the expediency for students to acquire the skills to use software tools, the use of which gives the opportunity to form their information competence, to implement pedagogical methods of individualization and differentiation of their educational activities. The aim of the paper is to show the expediency and necessity of using the elements of computer simulation while learning Physics as a basis for the formation of information competence of the student. The main research methods were aimed at establishing the level of information competence of students using the elements of computer simulation in Physics lessons. The approach to the use of computer simulation elements in Physics lessons is considered, in particular, when studying the section “Atomic nucleus. Nuclear Energy” in the 9th form of general secondary education institutions.It has been found out that the study of Physics using the elements of computer simulation allows to increase the students’ interest in learning physical phenomena and processes, the level of mastering knowledge through the use of visual means of educational materials, to stimulate the development of cognitive activity and creative thinking, which in general will promote the formation of the information competence level in students. Based on the experimental study, it was found that the process of forming the students’ information competence using the elements of computer simulation has ensured the high achievements for the majority of students of the experimental class.